MOTOR LEARNING CHILDREN WITH DOWN SYNDROME - Elena BALINT1 (Editura Universitatii Transilvania din Brasov, 2019)
In conducting the study we started from the hypothesis that the development of a special and effective teaching strategy using wellsystematic methods and means together with clearly formulated objectives, we will be able to teach the child / young man with Down syndrome to know him and the environment, forming motor skills that will help him adapt more easily and efficiently to the environmental conditions in which he lives. For evaluation we used the tests: Romberg, unipodal, Wells and Dillon, talocrural mobility test, Ruffier, psycho-motor coordination, sticks test, coordination test (Denisiuk).